Picking up the Pieces: Contextualizing Utilized Blade Fragments from Two Assemblages in Southwest Norway - Redmond, James; Scheie Eilertsen, Krister (In Situ Archaeologica, 2020)
This article centers on a discussion of blade fragments from two Late Mesolithic assemblages recovered during a recent excavation project in Rogaland, southwest Norway. Analysis undertaken during post excavation cataloging of lithic artefacts suggests some retouched and edge damaged pieces, represent minimally modified tools. The temporal context of the Sola finds offers an opportunity to reorientate research related to the northeast European/‘Post-Swiderian’ technological complex of which such tools were a central component. The studied fragments suggest that the two closely spaced areas may represent specialized, broadly contemporary activity. The results of this preliminary study highlight the latent interpretive potential of this relatively abundant yet somewhat intractable artefact class.